Risk Factors Associated with Suspected Clostridium difficile Infection (CDI) in Elderly Diarrhea Patients at Prof. Dr. I.G.N.G. Ngoerah Hospital - Aryana, I Gusti Putu Suka; Budayanti, Ni Nyoman Sri; Wedari, Ni Luh Putu Harta (Indonesian Journal of Tropical and Infectious Disease, 2023)
Clostridium difficile infection (CDI) is a typical healthcare-associated infection that contributes to a significant proportion of morbidity and mortality among hospitalized patients. Anaerobe microbiological laboratory examinations cannot be performed at Prof. Dr. I.G.N.G. Ngoerah Hospital, leading to many undetected cases; therefore, it is crucial to determine the risk factors. Identification  of cases may help to prevent, recognize, and  appropriately treat CDI, reducing morbidity and mortality. This study aimed to determine the risk factors associated with suspected CDI in elderly patients with diarrhea due to their vulnerability to immunosenescence. This research used medical records as secondary data to determine the risk factors associated with suspected CDI in elderly diarrhea patients at Prof. Dr. I.G.N.G. Ngoerah Hospital during the year period of 2017 to 2021 with total of 70 samples who met inclusion criteria by purposive sampling technique. One hundred percent of all samples had a history of hospitalization for ³ 48 h. There were 53 patients (77.1%) had a history of antibiotic use, 26 (37.1%) proton pump inhibitors (PPIs), 66 (94.3%) chemotherapy, 66 (94.3%) urinary tract infections, 6 (8.6%) kidney disease, and 7 (10%) myocardial infarction. Seven (10%) patients had vascular disease, and 11 (15.7%) had diabetes mellitus. Risk factors associated with suspected CDI in elderly patients with diarrhea at Prof. Dr. I.G.N.G. Ngoerah Hospital include hospitalization ³ for 48 hours, use of antibiotics in the last few months, proton pump inhibitors, decreased immune system, urinary tract infection, kidney disease, myocardial infarction, vascular disease, and diabetes mellitus.